Effect of the waste bottom ash strengthened the problematic clay soil: The use of by-product material - Ng, Jun Shen; Muzamir, Hasan; Nabilah, Md Mashod Fakeh (Faculty of Engineering, Khon Kaen University, 2025)
The extraction of industrial by-products such as bottom ash from power plants to the research areas can be lucrative for the economy and environment. In the civil engineering field, the soil condition which is filled with abundant soft clay soil has always been a problematic issue. Previous studies examined the available techniques of ground improvement for instance the installation of a granular pile is an efficient method to treat the soft clay soil, resolving the detrimental issues of lower value of soil’s bearing capacity, soil settlement occurrence, greater compressibility, and erodibility. Coherent to that, this research deployed the Vibro-replacement technique in fabricating the single bottom ash column beneath the clay soil to rectify the weak engineering properties of clay soil. The raw kaolin clay and bottom ash were examined through the geotechnical approaches, the distribution of particle size (PSD), Atterberg limit, relative density, pycnometer, hydrometer, falling head, constant head, and standard proctor. Via the Unconfined Compression Test (UCT), 20 specimens from unreinforced and reinforced categories were investigated. The average shear strength value from 5 identical specimens was utilized, considering the Column Penetrating Ratio (CPR), Column Height to Column Diameter Ratio (HDR), and Column Volume Replacement Ratio (CVR). The maximum shear strength improvement occurred in the S1680 sample, recorded at 58.66% at the CPR (0.8), HDR (5.00), and CVR (8.19%). Hence, the research findings verified that bottom ash as a sustainable material can raise the clay’s strength effectively.